Comparison of different culture media and storage temperatures for the long-term preservation of Streptococcus pneumoniaein the tropics - Siberry George; Brahmadathan K.N; Pandian Rajeswar; Lalitha M.K; Steinhoff Mark C.; John T. Jacob (The World Health Organization, 2001)
OBJECTIVE: The preservation of Streptococcus pneumoniae by standard freezing methods for subsequent tests - such as serotyping and antibiotic susceptibility - is not possible or is difficult in many developing countries because of the high cost of equipment, inadequate equipment maintenance, and irregular power supply. We evaluated alternative low-cost methods, by comparing different culture media and storage temperatures. METHODS: Clinical isolates of five capsular types (1, 5, 7, 19, and 23) of S. pneumoniae were preserved in rabbit blood, sheep blood, skimmed milk, or glycerol-chocolate broth, and stored at -20 masculineC or -70 masculineC. The cultures were also preserved by lyophilization or sand desiccation, followed by storage at room temperature and 4 masculineC. The viability of the preserved cultures was determined by making serial colony counts on day 0 and after 1 week, 4 weeks, 4 months and 16 months. The viability of cultures preserved by sand desiccation and storage at 4 masculineC was also determined every 6 months for up to 68 months. FINDINGS: Irrespective of the media used, cultures maintained at -20 masculineC became nonviable by the fourth month, while those maintained at -70 masculineC were still viable at 16 months. Cultures preserved by lyophilization or sand desiccation lost their viability by the fourth month when maintained at local room temperature (30-42 masculineC), but remained viable when stored at 4 masculineC for up to 68 months. CONCLUSION: Our results confirm that freezing at -70 masculineC, or lyophilization and storage at 4 masculineC are the ideal methods for the preservation of S. pneumoniae. In laboratories where lyophilization is not feasible, sand desiccation and storage at 4 masculineC offers an alternative low-cost method for the long-term preservation of S. pneumoniae.